2017
DOI: 10.3390/rs9090865
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Use of Remote Sensing and Social Sensing Data in Fine-Grained Urban Land Use Mapping: A Case Study in Beijing, China

Abstract: Abstract:In light of the need for fine-grained, accurate, and timely urban land use information, a per-field classification approach was proposed in this paper to automatically map fine-grained urban land use in a study area within Haidian District, Beijing, China, in 2016. High-resolution remote sensing imagery and multi-source social sensing data were used to provide both physical and socioeconomic information. Four categories of attributes were derived from both data sources for urban land use parcels segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 48 publications
(74 reference statements)
0
60
0
Order By: Relevance
“…At last, the proposed concept can be further extent to different types of RS images and applications. RS image segmentation is indispensable to measure urban metrics [66,67], to monitor landscape changes [68] and to model the pattern and extent of urban sprawl [69]. It is also important to define urban typologies [5], to classify land use [4], to manage urban environment [2] and to support sustainable urban development [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…At last, the proposed concept can be further extent to different types of RS images and applications. RS image segmentation is indispensable to measure urban metrics [66,67], to monitor landscape changes [68] and to model the pattern and extent of urban sprawl [69]. It is also important to define urban typologies [5], to classify land use [4], to manage urban environment [2] and to support sustainable urban development [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Pei et al [22] utilized the mobile phone dataset and a semi-supervised clustering method to classify different land-use types, and the detection rate of land-use reached 58.03%. Zhan, Ukkusuri, and Zhu [23] successfully explored the possibility and validity of using social media check-in dataset to classify land-use types.Meanwhile, many classification methods have also been widely developed to classify land use types and urban functional zones, such as K-Nearest Neighbors [24], Decision Tree [25], Support Vector Machine (SVM) [1,26], and Random Forest [19,27]. For instance, DeFries, Hansen, Townshend, and Sohlberg [28] used the Decision Tree algorithm to classify global land cover of 8 × 8 km resolution, which achieved an accuracy of over 80%.…”
mentioning
confidence: 99%
“…Although SVM is able to deal with high-dimensional and nonlinear problems, the uncertainty caused during the model training process due to its sensitivity to the initial parameters should also be noted. The Random Forest algorithm, a nonparametric classification model, is effective in obtaining accurate and stable predictions and reducing overfitting through building and merging multiple decision trees together [32], and was quite popular for land use and urban functional zones classification studies in past years [27,[33][34][35]. Yao et al [19] used the greedy algorithm, Random Forest algorithm and CBOW-based Word2Vec model to identify urban land use types based on POI data with an accuracy of 87.28%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some POI categories are closely related to human activities and more attractive to population, while other categories of POIs are less attractive to the population and even have a reject effect. This allows POIs to analyze the social lifestyle of humans and estimate population distribution [29,[38][39][40][41][42][43][44][45]. In recent years, many studies have demonstrated the usefulness of POI data in generating fine-grained population maps.…”
mentioning
confidence: 99%